Dante in T.S. Eliot's Four Quartets Vision, Mysticism, and the Mind's Journey to God - Aresi, Anna (2016)
This article develops a parallel reading of select passages from Eliot's Four Quartets and Dante's Comedy, highlighting a new relation between the two works. Since the structure of Dante's journey is best understood through the work of Bernard of Clairvaux, the article begins with a brief exposition of Bernard's theory of contemplation and the role it plays in Dante. Once the structure at work in Dante's Comedy becomes apparent, it is possible to observe the same structure at work in Four Quartets. In the second part of the article, on this basis, I propose my reading of the two works, arguing that, like the Comedy, the Quartets is an intellectual and spiritual journey starting from a basis in material reality and arriving, through philosophy and by grace, at the contemplation of the divine.